OPTICAL BIOSENSORS BASED ON HYBRID NANOSTRUCTURES AND METAMATERIALS - Kostyukevych, K. V.; Kryuchyna, Ye. A.; Kryuchyn, A. A.; Kostyukevych, S. O. (Medical Informatics and Engineering, 2021)
Background. The work is devoted to the study of methods for improving optical biosensor devices based on surface plasmon resonance (PPR) and surface-enhanced Raman scattering (SERS) using hybrid nanostructures and metamaterials. The aim of the study was to analyze the current state, problems and prospects of increasing the sensitivity of optical biosensors using hybrid nanomaterials and embossed nanostructures. Materials and methods. Theoretical analysis and generalization, systematization of research results using such leading scientometric databases as ScienceDirect, PubMed, Emerald, IEEE Xplore, Taylor & Francis, printed scientific articles for the period from 2009 to 2020 on keywords biosensors, surface plasmon resonance, relief structures, sensitivity of biosensors, including in Ukrainian and Russian translations. Results. Schemes of using hybrid magnetic-plasmon nanoparticles, bimetallic and dielectric multilayer films, diffraction structures, CD disks and Fano-resonant metamaterials are considered. Expanding the use of optical biosensors and conducting research at a qualitatively new level is possible only by significantly increasing their sensitivity. To solve this problem, it is necessary to develop new nano and metamaterials, as well as to use hybrid nanostructures specially created on their basis. The use of nanomaterials can significantly increase the sensitivity of biosesors based on surface plasmon resonance (PPR) and Raman scattering (SERS and SEIRA technologies). Effective, highly sensitive, high-performance optical biosensors can be created using microrelief structures based on CD technology. Conclusions. Optical biosensors, which allow the detection of a small amount of a substance and can be adapted to the analysis and detection of a large number of different biological and chemical objects, have become the most widespread. To increase the sensitivity of biosensors based on the method of surface-enhanced Raman scattering (SERS) use spectroscopy of surface-enhanced infrared absorption metal (SEIRA) using plasmon nanoantennas or metamaterials. In such hybrid structures, a significant local amplification of the near-field oscillatory mode of biomolecules is provided by specially designed plasmon nanoantennas, and the close connection of plasmon modes and oscillatory modes of molecules further enhances the SEIRA detection signal.